The Impact of Carbon Trading, Firm Size, Profitability, and Leverage on Company Value - Tohap Parulian; Muhammad Yamin Siregar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to understand how carbon trading activities and other financial factors collectively influence firm value in a business context that is increasingly concerned with sustainability issues. This study is quantitative, employing Structural Equation Modeling (SEM) analysis using Smart PLS 3.0. The population and sample comprise consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2022. A purposive sampling technique was used to select 131 companies. Data were collected through annual financial reports obtained from the Indonesia Stock Exchange and their official websites. This study consists of independent variables and dependent variables. The results show a significant negative relationship between carbon trading activities and firm value. This means that the more active a company is in carbon trading, the lower its firm value. There is a significant positive relationship between firm size and firm value. Larger companies tend to have higher firm values. There is a significant positive relationship between profitability and firm value. More profitable companies tend to have higher firm values. There is no significant relationship between leverage and firm value.